Two Cases of Worsening Psoriasis After Switching From Ustekinumab to Guselkumab. Issue 3 (July 2019) - Casseres, Rachel G.; Rosmarin, David
Introduction: Guselkumab is an Interleukin-23 inhibitor that has been shown to be effective for the treatment of psoriasis even in patients with an inadequate response to ustekinumab. At this time, there are no published reports of worsening psoriasis or psoriatic arthritis on guselkumab compared to ustekinumab. Methods: We reviewed the charts of two patients with psoriasis who were treated in our clinic with guselkumab after failing treatment with ustekinumab. Results: The patient in case 1 experienced a psoriasis flare after switching from ustekinumab to guselkumab. The patient in case 2 has an increase in body surface area of her psoriasis as well as worsening joint symptoms while on guselkumab compared to ustekinumab. Discussion: Not all patients will have a superior response to guselkumab than ustekinumab.